2014
DOI: 10.1016/j.jacl.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

National Lipid Association recommendations for patient-centered management of dyslipidemia: Part 1 – executive summary

Abstract: Various organizations and agencies have issued recommendations for the management of dyslipidemia. Although many commonalities exist among them, material differences are present as well. The leadership of the National Lipid Association (NLA) convened an Expert Panel to develop a consensus set of recommendations for patient-centered management of dyslipidemia in clinical medicine. The current Executive Summary highlights the major conclusions in Part 1 of the recommendations report of the NLA Expert Panel and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
393
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(414 citation statements)
references
References 52 publications
12
393
1
8
Order By: Relevance
“…Thereby, for patients with very high CV risk, namely those with documented ACVD, diabetes mellitus with organ damage, moderate to severe chronic kidney disease, or a calculated 10-year ACVD risk 10% according to Systemic COronary Risk Estimation (SCORE) [2,3], the current treatment target advocated for low density lipoprotein cholesterol (LDL-C) is set at 70 mg/dL (1.81 mmol/L) or at a 50% reduction from relative baseline levels [4,5]. These treatment targets for LDL-C are primarily based on results of a number of randomized clinical trials (RCTs) performed over the last two decades, which reported substantial clinical benefits in terms of risk reduction by this treat-to-target approach in various subgroups of patients at very high CV risk [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, for patients with very high CV risk, namely those with documented ACVD, diabetes mellitus with organ damage, moderate to severe chronic kidney disease, or a calculated 10-year ACVD risk 10% according to Systemic COronary Risk Estimation (SCORE) [2,3], the current treatment target advocated for low density lipoprotein cholesterol (LDL-C) is set at 70 mg/dL (1.81 mmol/L) or at a 50% reduction from relative baseline levels [4,5]. These treatment targets for LDL-C are primarily based on results of a number of randomized clinical trials (RCTs) performed over the last two decades, which reported substantial clinical benefits in terms of risk reduction by this treat-to-target approach in various subgroups of patients at very high CV risk [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, reducing elevated levels of atherogenic cholesterol particles has been recommended to lower ASCVD and can be achieved by atherogenic cholesterol lowering through multiple modalities, including lifestyle and drug therapies. The intensity of risk-reduction therapy should be individualised based on the patient's absolute risk for an ASCVD event and, both intermediate-term and long-term/lifetime risk should be considered when assessing the potential benefits and hazards of riskreduction therapies [14]. Both NLA and ACC/AHA recommend statin treatment as the mainstay of drug therapy to reduce ASCVD risk in patients who have been considered for treatment with lipid-lowering drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines represented a major paradigm shift and sparked considerable controversy because they abandoned the traditional treat-to-target approach [33]. Even though the strategy of treating patients to a specific level of LDL-C has never been formally tested in large trials assessing cardiovascular morbidity and mortality, treatment goals might still be useful as a means to ensure that the aggressiveness of therapy is matched to absolute risk for an event [34]. LDL-C levels achieved with treatment correlated well with the incidence of major atherosclerotic cardiovascular events in four meta-analyses [7][8][9]13] and a large analysis of 40,000 patient records [35].…”
Section: Inability Of Some Patients To Attain Desirable Low-mentioning
confidence: 99%
“…Besides their previously acknowledged role in hypercholesterolemia, statin-ezetimibe combinations are now indicated to reduce the risk of [58] Data indicate that combination therapy with EZE also brings a benefit that is in line with the CTT collaboration meta-analysis supporting the notion that LDL-C reduction is key to the achieved benefit Selective cholesterol absorption inhibitors (…) are recommended as combination therapy with statins in selected pts when a specific goal is not reached with the maximal tolerated dose of a statin More recent trial evidence shows a clear cardiovascular benefit of lowering LDL-C with EZE on top of a statin in pts with T2DM It must be stressed that the only combination with evidence of clinical benefit (one large RCT) is that of a statin combined with EZE. Based on the relatively limited body of evidence, clinicians may restrict the use of this combination to pts at high or very-high risk of CVD 2016 ACC Expert Consensus Decision Pathway on the Role of Non-Statin Therapies for LDLCholesterol Lowering in the Management of Atherosclerotic Cardiovascular Disease Risk [36] Stable clinical ASCVD, on statin for secondary prevention Although there is a gap in RCT evidence demonstrating outcomes benefits of using combination therapy in pts with stable clinical ASCVD, the expert consensus writing committee supports consideration of adding EZE 10 mg daily as the first non-statin agent, given the benefits on ASCVD outcomes and demonstrated safety of EZE in patients with ACS treated with EZE-SIM vs. SIM monotherapy Clinical ASCVD and baseline LDL-C C190 mg/dl not due to secondary causes, on statin for secondary prevention Although there is a gap in the evidence demonstrating outcomes benefit when combined with high-intensity statin therapy, the addition of EZE may be considered based upon the improved ASCVD outcomes and demonstrated safety of the combination of EZE with moderate-intensity SIM vs. SIM monotherapy In a patient with ASCVD and baseline LDL-C C190 mg/dl with\50% reduction in LDL-C (and may consider LDL-C C70 mg/dl) it is reasonable to consider a PCSK9 inhibitor as a first step rather than EZE or bile acid sequestrant given the greater LDL-C lowering efficacy of PCSK9 inhibitors Adults aged 40-75 years without ASCVD, but with diabetes and LDL-C 70-189 mg/dl, on statin for primary prevention EZE is the preferred initial non-statin therapy because of its tolerability, convenience, and single-tablet daily dose Adults aged 40-75 years without clinical ASCVD or diabetes, with LDL-C 70-189 mg/dl and an estimated 10-year risk for ASCVD of C7.5%, on statin for primary prevention For primary prevention pts with high-risk markers who have achieved a less-thananticipated response to maximally tolerated statin therapy with\50% LDL-C reduction (and may consider LDL-C C100 mg/dl), EZE (or a bile acid sequestrant as a secondline agent) may be considered as a potential additional agent 2015 National Lipid Association Recommendations for Patient-Centered Management of Dyslipidemia [34] Combination drug therapy with a statin plus a second (or third) agent that further lowers non-HDL-C and LDL-C may be considered for pts who have not attained their atherogenic cholesterol levels after the maximum tolerated statin dosage has been reached and for those who have contraindications or are intolerant to statin therapy 2015 ESC Guidelines for the Management of Acute Coronary Syndromes in Patients Presenting without Persistent ST-Segment Elevation [81] In pts with LDL-C C70 mg/dl despite a maximally tolerated statin dose, further reduction in LDL-C with a non-statin agent a should be considered. Class IIa recommendation, level of evidence B 2013 ACC/AHA Guideline on the Treatment of Blood Cholesterol to Reduce Atheroscleroti...…”
Section: Atorvastatin-ezetimibe Combinations: Approved Indications Anmentioning
confidence: 99%